2019
DOI: 10.1088/1755-1315/346/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Application of the technology of encapsulation of rowanberry extract to develop a functional cottage cheese dessert

Abstract: The possibility of using the technology of encapsulation of rowanberry extract to remove the natural bitter taste of raw material is discussed in this paper. Fruits of the rowan native to Novosibirsk city and the Altai region (Russia) were subjected to infrared (IR) drying (the rowanberries were collected in September 2017 and 2018). A plant extract produced using the IR-dried rowanberry powder was utilized for encapsulation. Two encapsulation technologies, spray drying and freeze drying, were discussed and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Pérez‐Soto et al ( 2021 ) also reported a significant increase in the phenol content and antioxidant activity of fresh cheese due to the incorporation of Opuntia oligacantha microcapsule and nano‐emulsion to cheeses. Matseychik et al ( 2019 ) also found that adding rowanberry extract capsules to cottage cheese dessert significantly increased antioxidant activity. Farrag et al ( 2020 ) demonstrated that in white fresh cheeses containing free olive polyphenols extract during the 30‐day storage period, the phenol content and antioxidant activity significantly decreased, but in cheeses containing encapsulated extract, no significant change in these functional parameters was observed over time.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Pérez‐Soto et al ( 2021 ) also reported a significant increase in the phenol content and antioxidant activity of fresh cheese due to the incorporation of Opuntia oligacantha microcapsule and nano‐emulsion to cheeses. Matseychik et al ( 2019 ) also found that adding rowanberry extract capsules to cottage cheese dessert significantly increased antioxidant activity. Farrag et al ( 2020 ) demonstrated that in white fresh cheeses containing free olive polyphenols extract during the 30‐day storage period, the phenol content and antioxidant activity significantly decreased, but in cheeses containing encapsulated extract, no significant change in these functional parameters was observed over time.…”
Section: Resultsmentioning
confidence: 96%
“…Flores‐Mancha et al ( 2021 ) demonstrated that the addition of beet extract‐loaded capsules to the yogurt had no significant effect on the pH and acidity, and during the storage, the pH values of samples decreased. Matseychik et al ( 2019 ) reported that the acidity value of cottage cheese dessert containing rowanberry extract capsules was higher than that of the control. In the study conducted by Balabanova et al ( 2020 ), the incorporation of encapsulated pepper extracts to the Labneh cheese did not show a significant effect on the pH and acidity of the samples, and the pH and acidity of cheeses decreased and increased during storage, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations